2010
DOI: 10.3109/19396368.2010.486470
|View full text |Cite
|
Sign up to set email alerts
|

Use of Human Embryonic Stem Cell-based Models for Male Reproductive Toxicity Screening

Abstract: Male reproductive toxicity examines harmful effects of various agents on all aspects and developmental stages of the male reproductive system, including germ cell development and spermatogenesis. In developing a model for reproductive toxicity screening it is important to define the developmental stage that this model is going to recreate in vitro and to identify critical molecular targets of this stage. In this review we focus our discussion on the potential for using embryonic stem cell (ESC)-derived models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
(90 reference statements)
0
6
0
Order By: Relevance
“…The obvious potential of combing stem cell methods with Tox-21c approaches was stressed earlier (Chapin and Stedman, 2009). This extends from embryotoxicity to other areas such as male fertility (Krtolica and Giritharan, 2010) and to link toxicity related biomarkers uncovered using hES cells with the PoT concept. However, the vision of Tox-21c is not that a tremendous number of assays in a centralized facility are used for each and every substance.…”
Section: Pathways Of Toxicity (Pot) and Systems Toxicologymentioning
confidence: 99%
“…The obvious potential of combing stem cell methods with Tox-21c approaches was stressed earlier (Chapin and Stedman, 2009). This extends from embryotoxicity to other areas such as male fertility (Krtolica and Giritharan, 2010) and to link toxicity related biomarkers uncovered using hES cells with the PoT concept. However, the vision of Tox-21c is not that a tremendous number of assays in a centralized facility are used for each and every substance.…”
Section: Pathways Of Toxicity (Pot) and Systems Toxicologymentioning
confidence: 99%
“…29,[72][73][74] ES cell-based approaches to study germ cell development have been shown to be useful tools for the direct examination of the effects of environmental toxicants on the molecular regulation of human germ cell formation. 30,31 Very recently, we found that mercury and lead can affect the biological properties of human AFS cells. 75 The differentiation of AFS cells into cell of the germ cell lineage would allow to investigate the role of these two toxicants on human male germ cell development, but also to screen additional substances for their toxic potential for spermatogenesis.…”
Section: Amniotic Fluid Stem (Afs) Cells Could Be a Useful Tool To Stmentioning
confidence: 99%
“…27,28 It is well known that spermatogenesis is a complex biological process, which is particularly sensitive to environmental insults, such as toxicants, 29 and stem cell-based in vitro models have already been used for reproductive toxicity screening. 30,31 …”
Section: Introductionmentioning
confidence: 99%
“…hESC‐based in vitro models have been developed to assess reproductive toxicity based on the genetic and epigenetic changes that occur during germ cell development and to screen the ability of known agents to disrupt germ cell development (Rugg‐Gunn et al ., ). It could be useful to establish an in vitro model to replicate the in vivo development of human male gametes, such as their differentiation into primordial germ cells, generation of spermatogonial stem cells and formation of spermatozoa, to understand and study adverse effects on the male reproductive system (Krtolica & Giritharan, ). The beneficial aspects of stem cells in toxicology and compatibility have promoted the commercialization of hESC‐based in vitro platforms (Pouton & Haynes, ; Sinha, ).…”
Section: Introductionmentioning
confidence: 99%